Identifying challenges in quantifying uncertainty: case study in infrared thermography - Grenyer, Alex; Addepalli, Sri; Zhao, Yifan; Oakey, Luke; Erkoyuncu, John Ahmet; Roy, Rajkumar (Elsevier, 2018)
Complex engineering systems present a wealth of uncertainties concerning aspects ranging from performance measurements to maintainability and through-life characteristics. A quantifiable understanding of these uncertainties is vital to system optimisation and plays a key role in decision-making processes for manufacturing organisations worldwide; impacting profit, product availability and manufacturing efficiency. The aim of this paper is to examine challenges and complications that arise when quantifying uncertainties in complex engineering systems that rely on expert opinion. A thermographic inspection system is utilised as a use case. Contractor-client and supervisor-maintainer relationships are examined. Key challenges highlighted involve accurate depiction of error margins and corresponding uncertainties of components where data is only heuristically obtainable, as well as the influence of environmental conditions and skill of the maintainer.
Keywords: Uncertainty quantification; Challenges; Insustrial Product Service System; Complex engineering system; Thermography